Handbook on social stratification in the BRIC countries : change and perspective - Li, Peilin (Singapore : World Scientific, 2013)
Along with the fast growing economy, the term'BRICs' was coined to represent the newly emerging countries of Brazil, Russia, India and China. The enhanced economy in these countries has largely improved people's lives; at the same time, it has also strongly influenced the transformation of social structure, norms and values. This book examines specifically the changes in each society from the perspective of social stratification, with topics covering the main social classes, the inequality of education and income, the different styles of consumption as well as the class consciousness and values.
Includes bibliographical references (p. 771-818) and index.
Keywords: Social classes -- BRIC countries; Social stratification -- BRIC countries; Social change -- BRIC countries; BRIC countries -- Social conditions